2012
DOI: 10.1523/jneurosci.3662-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Bilateral Neuronal Network Reorganization and Functional Recovery in Relation to Stroke Severity

Abstract: Remodeling of neuronal structures and networks is believed to significantly contribute to (partial) restoration of functions after stroke. However, it has been unclear to what extent the brain reorganizes and how this correlates with functional recovery in relation to stroke severity. We applied serial resting-state functional MRI and diffusion tensor imaging together with behavioral testing to relate longitudinal modifications in functional and structural connectivity of the sensorimotor neuronal network to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
162
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(193 citation statements)
references
References 52 publications
23
162
1
3
Order By: Relevance
“…Previous studies have demonstrated that cortical brain infarcts can lead to cortical WM network remodeling. 31 However, it is unclear whether disruption of cortical WM networks occurred in patients with subcortical silent brain infarcts. In this report, specific attention was directed toward the disruption of cortical WM networks in patients with brain infarcts located in the basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that cortical brain infarcts can lead to cortical WM network remodeling. 31 However, it is unclear whether disruption of cortical WM networks occurred in patients with subcortical silent brain infarcts. In this report, specific attention was directed toward the disruption of cortical WM networks in patients with brain infarcts located in the basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques, such as intrinsic optical imaging, VSD imaging, and 2-photo calcium imaging, have been used in conjunction with forelimb stimulations to study post-stroke activation patterns and functional remapping. Remapping occurs after stroke most prominently in peri-infarct zones, but is also observed in connected regions such as the unaffected hemisphere (e.g., contralesional cortex) [13,82,139,143,144]. Remodeling in peri-infarct zones and in the unaffected hemisphere, such as loss and recovery of dendritic spines and axonal sprouting, has been reported [12,145,146].…”
Section: Optogenetic Interrogation Of Post-stroke Remapping and Recoverymentioning
confidence: 98%
“…In addition, by combining fMRI in the same rats they reported a transhemispheric fiber connection through the corpus callosum that was lost in the rats without recovery of BOLD signals at 5 weeks after stroke. Van Meer et al [143] applied serial diffusion tensor imaging and resting-state fMRI, in which no stimulus was applied but the spontaneous BOLD fluctuations were analyzed, in order to correlate white matter integrity and functional connectivity to stroke recovery. Similar to a scenario described in patients, improvement of sensorimotor function is correlated with restoration of interhemispheric functional connectivity and normalization of network configuration of the bilateral sensorimotor cortex.…”
Section: Multimodal Approaches Using Optogenetics and Other Techniquementioning
confidence: 99%
“…В последствии было подтверждено, что снижение межполушарных взаимосвязей между ипсилатеральными и контралатеральными регио-нами первичной сенсомоторной коры, связано с уменьшением транскаллозальной передачи мар-ганца в этих областях [36]. Используя опытную модель инсульта, было показано, что степень функционального восстановления после ишемии связана со степенью сохранения или поражения кортикоспинальных трактов на стороне поврежде-ния в сочетании с восстановлением нейрональных сигналов, межполушарной синхронизации и норма-лизации функции коры [37]. Аналогично экспери-ментальной модели, подобные изменения функ-циональных взаимосвязей в состоянии покоя были выявлены и у больных непосредственно после перенесенного инсульта, что выражалось в значи-тельном сокращении количества функциональных взаимосвязей, особенно межполушарных, из об-ласти сенсомоторной коры на стороне поврежде-ния [38].…”
unclassified
“…Авторы показали, что в нейронной сети мозга, в процессе восстанов-ления возникают изменения топологии с неопти-мальной конфигурацией сети. Однако в экспери-ментальной модели инсульта, наблюдается неод-нозначная картина изменения характеристик ней-ронной сети [37]. Установлено, что длина кратчайшего пути и расширение сети мотонейронов после инсульта у крыс, были значительно увеличенными в первые дни, затем они снижались до нормальных показа-телей.…”
unclassified